H.R. 1753 and S. 330, Methane Hydrate Research and Development Act of 1999 : hearing before the Subcommittee on Energy and Mineral Resources of the Committee on Resources, House of Representatives, One Hundred Sixth Congress, first session . May 25, 1999, Washington, DC. - United States. Congress. House. Committee on Resources. Subcommittee on Energy and Mineral Resources. (Washington : U.S. G.P.O. : For sale by the U.S. G.P.O., Supt. of Docs., Congressional Sales Office, 1999)
"Serial no. 106-32." Shipping list no.: 2000-0025-P. Distributed to some depository libraries in microfiche. Includes bibliographical references (p. 79). Microfiche. Microfiche. Mode of access: Internet.